Effect Of Enerosorption On Morphological Changes Of The Barrier-Protective Structures Of The Gastrointestinal Tract In Chronic Kidney Diseases And Uremia - Daminov B.T., Aripova D.Sh. Ruzmetova I.A. (International Journal of Advanced Science and Technology, 2020)
The gastrointestinal tract is an active dynamic system that implements a number of important life support processes [30,2,57,87,203]. The effects of ES on structures performing barrier-protective functions remain virtually unstudied.